Kebijakan Formulasi Pertanggungjawaban Pidana Pengguna Jasa Prostitusi Melalui Media Online - Korassa Sonbai, Alexander Imanuel (Acta Comitas : Jurnal Hukum Kenotariatan, 2019)
The phenomenon of online prostitution became a hot issue in Indonesia. Online Prostitution Article 27 paragraph (1) Jo. Article 45 paragraph (1) of the ITE Law, Article 296 of the Criminal Code, Article 506 of the Criminal Code, Article 2 paragraph (1) of Law No. 21 of 2007 concerning Eradication of Crime in Trafficking in Persons, and Article 30 Jo. Article 4 paragraph (2) Law No. 44 of 2008 concerning Pornography. However, in the article has not set explicitly against online prostitution service users. The aim of this study was to elaborate on the user settings prostitution service through online media and forms of criminal responsibility prostitution service users through online media. The method used is a normative legal research. This type of approach is used, among others: statue approach, conceptual approach, and comparative approach. The results of the study indicate that the formulation policy criminal liability for online prostitution service users has not yet been regulated in Indonesian legislation, from the results of a comparison with Sweden (Sex Purchase Act) also regulates the criminal liability of users of online prostitution services and should the rules in the future refer to Swedish law (sex purchase act) . Fenomena prostitusi online menjadi suatu isu hangat di Indonesia. Prostitusi online Pasal 27 ayat (1) Jo. Pasal 45 ayat (1) UU ITE, Pasal 296 KUHP, Pasal 506 KUHP, Pasal 2 ayat (1) UU No. 21 tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang, dan Pasal 30 Jo. Pasal 4 ayat (2) UU No. 44 tahun 2008 tentang Pornografi. Namun, dalam pasal tersebut belum mengatur secara eksplisit terhadap pengguna jasa prostitusi online. Tujuan studi ini ialah untuk mengelaborasi pengaturan pengguna jasa prostitusi melalui media online dan bentuk pertanggungjawaban pidana pengguna jasa prostitusi melalui media online. Metode penelitian yang digunakan adalah penelitian hukum normatif. Jenis pendekatan yang digunakan antara lain: pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan perbandingan. Hasil studi menunjukkan bahwa kebijakan formulasi pertanggungjawaban pidana pengguna jasa prostitusi online saat ini belum di atur dalam peraturan perundang-undangan Indonesia, dari hasil perbandingan dengan Swedia (Sex Purchase Act) mengatur juga pertanggungjawaban pidana pengguna jasa prostitusi online dan sebaiknya aturan di masa mendatang mengacu pada hukum swedia (sex purchase act)